Traffic Balancing Method in Shortest Path Routing - Mohamed Abdulqader, Makarem (2007)
Open Shortest Path First (OSPF) is the most commonly used intra-domain routing protocol. OSPF routes traffic flows along shortest paths and splits the load evenly at nodes where several outgoing links are on the shortest paths to the same destination. Shortest paths are defined based on a weight value assigned to each link in the network. OSPF routing suffers from un-utilizing network resources, and hence appearance of congested links. Congestion appears in OSPF routing due to the excessive usage of shortest paths where still other links with higher weight values are unutilized. Many load balancing approaches were proposed to avoid congestion and increase network utilization. One of these approaches argued that optimizing link weights will improve shortest path routing performance, thus no changing needed in underlying infrastructure. Weight optimization approach neither deal with the issue of load splitting, nor the tradeoff relation between exploiting network resources and avoiding congested points. Increasing balanced links may lead to a usage of congested links. On the other hand, avoiding congested links may lead to un-utilizing some uncongested links. This research has two main aims. The first aim is to study the tradeoff relation between utilizing network links and avoiding congested links. The second aim is to provide an unequal load splitting in the current widely deployed shortest path routing.